Physical activity is positively associated with college students' positive affect regardless of stressful life events during the COVID-19 pandemic. (January 2021) - Maher, Jaclyn P.; Hevel, Derek J.; Reifsteck, Erin J.; Drollette, Eric S.
Abstract: The study was designed to determine associations between physical activity (PA) and affect before and during COVID-19 stay-at-home orders and how change in PA predicted change in affect during this time. Before and during COVID-19 stay-at-home orders, college students (n = 107) completed assessments of PA, positive and negative affect, sleep quality, food insecurity, and stressful life events (during stay-at-home order only). Total minutes of PA was positively associated with positive affect before ( B = 0.01, p < 0.01) and during ( B = 0.01, p = 0.01) COVID-19 stay-at-home orders. Change in minutes of PA was positively associated with change in positive affect ( B = 0.01, p = 0.01). Associations between PA and positive affect were not moderated by stressful life events. PA only predicted negative affect before COVID-19 stay-at-home orders ( B = −0.003, p = 0.04). PA appears to enhance positive affect during a global pandemic. Findings have implications for PA as a tool for maintaining or enhancing mental health during a time of trauma and uncertainty. Highlights: Physical activity and positive affect decreased during the COVID-19 pandemic. Negative affect increased during the COVID-19 pandemic. Majority of participants experienced clinically meaningful levels of stressful life events during the pandemic. Physical activity was associated with positive affect before and during the pandemic. Physical activity was associated with negative affect before the pandemic only.